Impact of switching from different treatment regimens to a fixed-dose combination pill (polypill) in patients with cardiovascular disease or similarly high risk: The influence of baseline medication on LDL-cholesterol, blood pressure and calculated risk reduction when switching to a cardiovascular polypill. (29th August 2020) - Lafeber, Melvin; Spiering, Wilko; Visseren, Frank LJ; Grobbee, Diederick E; Bots, Michiel L; Stanton, Alice; Patel, Anushka; Prabhakaran, Dorairaj; Webster, Ruth; Thom, Simon; Rodgers, Anthony; ,
Abstract: Aims: Cardiovascular fixed-dose combination pills, or polypills, may help address the widespread lack of access and adherence to proven medicines. Initiation of polypill-based care typically entails switching from current separately taken medications. Given the heterogeneity in usual care, there is interest in the impact of polypill treatment across different patterns of prior medication regimen. Methods: A total of 2004 participants with established cardiovascular disease or estimated 5-year cardiovascular risk of over 15% were randomised to polypill-based treatment (aspirin 75 mg, simvastatin 40 mg, lisinopril 10 mg and either atenolol 50 mg or hydrochlorothiazide 12.5 mg) or usual care. Baseline medications were classified by potency relative to polypill components. Estimated cardiovascular risk reduction was calculated by combining risk factor changes with results seen in meta-analyses of previous randomised trials. Results: For cholesterol reduction conferred by polypills, there was a dose response across baseline statin groups, with mean low-density lipoprotein (LDL)-cholesterol differences of 0.37, 0.22, 0.14 and 0.07 mmol/L among patients taking no statin, less potent, equipotent and more potent statin at baseline, respectively. Similarly there were differences in mean systolic BP of 5.4, 6.2, 3.3 and 1.8 mmHg among patients taking 0, 1, 2 or 3 BP-lowering agents. Among patients taking more potent statins at baseline, there was no significant difference in LDL-cholesterol but there were benefits for BP and aspirin adherence. Similar results were seen among patients taking 3 BP-lowering agents at baseline. Switching to a polypill-based strategy resulted in estimated cardiovascular relative risk reductions across a wide range of usual care patterns of antiplatelet, statin and BP-lowering therapy prescribing. Conclusion: Adherence benefits from switching to a polypill resulted in risk factor changes that were at least as good as usual care across a wide variety of treatment patterns, including equally potent or more potent regimens. The benefits of switching to polypill-based care were greatest among those stepped up from partial treatment or less potent treatment.